(untitled) (Basel Institute on Governance Working Papers, 2024)
At the 8th session of the Conference of the States Parties to the United Nations Convention against Corruption (UNCAC), in December 2019, States parties adopted a resolution recognising the relationship between corruption and environmental crimes. Resolution 8/12 – Preventing and combating corruption as it relates to crimes that have an impact on the environment – is a landmark Resolution. With its 23 operative paragraphs (OPs), it underlies the importance of addressing corruption linked to crimes that have an impact on the environment. It urges States parties to prevent, investigate and prosecute corruption offences where they may be linked to crimes that have an impact on the environment. This Working Paper report presents a concise overview of prevention and enforcement actions, initiatives and measures implemented by UNCAC States parties between 2019 and 2023 to combat corruption as it pertains to crimes that have an impact on the environment. Section 2 focuses on prevention and Section 3 on enforcement actions. Section 4 underscores the valuable contributions made by non-state actors, in particular civil society, academia and the media in this collective endeavour. The conclusion includes a list of promising initiatives for corruption prevention and enforcement.